THE ROLE OF BUREAUCRATIC REFORM IN ENHANCING PUBLIC SERVICE QUALITY: EVIDENCE FROM EAST JAVA - Ami Dwi Wijayanti; Fedianty Augustinah; Dian Ferriswara (Yayasan Nuraini Ibrahim Mandiri, 2025)
Bureaucratic reform is a critical strategy to improve the quality of public services by promoting transparent, efficient, and accountable governsance. This study aims to analyze the role of bureaucratic reform in enhancing public service delivery, focusing on the implementation of good governance principles, digitalization, and the development of bureaucratic capacity. Using a qualitative descriptive approach, data were collected through literature review, policy analysis, and in-depth interviews with relevant stakeholders. The findings indicate that the bureaucratic reform efforts in East Java Province have led to a significant increase in the Bureaucratic Reform Index, the strengthening of Electronic-Based Government Systems (SPBE), and a measurable impact on service quality and poverty alleviation. The digital transformation of public services has enabled more accessible, faster, and transparent service delivery to citizens. Nevertheless, challenges such as bureaucratic resistance, limited digital infrastructure, and inadequate human resource competencies remain. Therefore, a stronger commitment and continuous innovation are required to build a professional, adaptive, and citizen-oriented public bureaucracy.